Polynomial structure of Benzene ring embedded in periodic-type surface in 2-dimension - Zobair, Mian Muhammad,; Shaker, Hani,; Imran, Muhammad,; Rehman, Noor, (Utilitas Mathematica, 2018)
The counting polynomials are valuable topological portrayal of aromatic structures. The quasi orthogonal cuts (qoc) strips enable us to represent the multi-structural properties of nanostructures. It likewise portrays its topological invariants by virtue of quasi-orthogonal cuts in these graphs. In this article, we give a total depiction of the Omega, Sadhana, PI and theta polynomial of the benzene ring which is embedded in a periodic-type surface in 2-dimension and give its numerical confirmation. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.